2015
DOI: 10.1016/j.neuron.2015.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin Interneurons of Hippocampus Tune Population Activity at Theta Frequency

Abstract: Hippocampal theta rhythm arises from a combination of recently described intrinsic theta oscillators and inputs from multiple brain areas. Interneurons expressing the markers parvalbumin (PV) and somatostatin (SOM) are leading candidates to participate in intrinsic rhythm generation and principal cell (PC) coordination in distal CA1 and subiculum. We tested their involvement by optogenetically activating and silencing PV or SOM interneurons in an intact hippocampus preparation that preserves intrinsic connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
233
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 222 publications
(257 citation statements)
references
References 40 publications
24
233
0
Order By: Relevance
“…These inhibitory neurons expressing PV and SOM, among the most affected populations impacted by aging in the hippocampus (26,27,31,59,60), have been shown to play important roles in learning and memory operations (28)(29)(30)(31)61). As our memory-guided learning task plausibly engages hippocampal processes, the positive changes recorded in inhibitory neuronal populations presumably reflect the fact that our simple form of training has induced physical and functional changes that have had positive, generalized impacts expressed very broadly across forebrain networks.…”
Section: Discussionmentioning
confidence: 91%
“…These inhibitory neurons expressing PV and SOM, among the most affected populations impacted by aging in the hippocampus (26,27,31,59,60), have been shown to play important roles in learning and memory operations (28)(29)(30)(31)61). As our memory-guided learning task plausibly engages hippocampal processes, the positive changes recorded in inhibitory neuronal populations presumably reflect the fact that our simple form of training has induced physical and functional changes that have had positive, generalized impacts expressed very broadly across forebrain networks.…”
Section: Discussionmentioning
confidence: 91%
“…The firing of action currents in mouse hippocampal neurons was greatly increased upon CNO exposure. As most of these PV-positive interneurons are GABAergic interneurons (GABA, γ-aminobutyric acid) [2], it is possible that activation of these inhibitory neurons may yield increased inhibition in activity of excitatory neurons in the DG [49-51]. Indeed, hM3D-Gq was expressed in PV-positive neurons in Cre-mice that received lentiviral injection and CNO administration.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, KA elicited a significant decrease in neuronal density in calpain-1 KO mice, suggesting perhaps that the restricted activation of calpain-1 in WT mice in parvalbumin-containing interneurons, and to a lesser extent in CCK-containing interneurons, could nevertheless be involved in the neuroprotection of CA1 and CA3 neurons. It has recently been reported that parvalbumin-containing interneurons are critical for pyramidal cell synchronization of firing and the emergence of hippocampal theta rhythm (Amilhon et al, 2015). It is tempting to speculate that, by protecting these interneurons from KA-mediated neurodegeneration, calpain-1 activation maintains a sufficient degree of inhibition throughout the hippocampal circuitry to limit the extent of neurodegeneration in the pyramidal cells they innervate.…”
Section: Discussionmentioning
confidence: 99%